2021
DOI: 10.1007/s11469-021-00550-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19 Fear on Society’s Quality of Life

Abstract: The COVID-19 pandemic is an important factor affecting the health of people worldwide, as well as a source of fear, stress, and anxiety. The aim of this study was to determine the level of fear caused by the COVID-19 pandemic in Turkish society and evaluate its effects on quality of life. The sociodemographic information form, COVID-19 Fear Scale (FCV-19S), and WHOQOL-BREF Quality of Life Scale were applied to the participants. A total of 705 people, who were accessed via the internet, responded willingly to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 23 publications
(45 reference statements)
5
21
1
Order By: Relevance
“…In such unforeseen situations, family support is important to motivate people to continue working [ 13 , 36 ]. Married workers can connect more closely with their families, share things beyond work, and vent emotions better [ 37 ]. This finding indicates that single nursing professionals may need more psychological support.…”
Section: Discussionmentioning
confidence: 99%
“…In such unforeseen situations, family support is important to motivate people to continue working [ 13 , 36 ]. Married workers can connect more closely with their families, share things beyond work, and vent emotions better [ 37 ]. This finding indicates that single nursing professionals may need more psychological support.…”
Section: Discussionmentioning
confidence: 99%
“…Convergent validity was calculated using the Spearman’s rank correlation coefficients of the FCV-19S with the rest of the applied measures. Based on previous studies, a moderate correlation (rS = 0.30−0.50) [ 38 ] was hypothesized between the FCV-19S and emotional wellbeing (PANAS-Balance) [ 39 , 40 ], resilience (BRCS) [ 41 ], depression (GDS-5) [ 23 ] and quality of life (FUMAT-24) [ 42 ].…”
Section: Methodsmentioning
confidence: 99%
“…The novel coronavirus-2019 (COVID- 19) pandemic not only attacked our bodies, but also seriously affected the society's quality of life. 1 Many studies have confirmed that COVID-19 pandemic has significantly increased anxiety level. [2][3][4][5][6] Recent studies have demonstrated that the lockdown due to COVID-19 would reduce sleep quality and physical activity levels, [7][8][9][10][11] which in turn could increase the anxiety level.…”
Section: Introductionmentioning
confidence: 99%